Calculation of Elongation in Media Use Backing Ceramic against Steel ASTM A36 by SMAW Process - Juswan Sade (Collaborate Engineering Daily Book Series, 2023)
Process Welding is usually done back and forth to get maximum results; of course, this will save time and increase costs. A medium backing ceramic is used to minimize the time a welder uses and the costs used. In the welding process, it will only partially get good results. Therefore, researchers will look for solutions to problems to maximize better welding. Therefore this research made to know the effect value of useBacking ceramic and not useBacking ceramic against ASTM A36 steel using SMAW welding using elongation calculations. Influence of media use backing ceramic on the strength of the tensile test on ASTM A36 steel using SMAW welding using elongation calculation is known that the highest elongation values ​​were found in specimens that did not use Backing ceramic by 8.80%. At the same time, the lowest elongation value is found in the specimen that uses Backing ceramic by 7.30%.